Influence of Sugar Cane Mechanical Harvest on Clear Juice Quality at Elguneid Sugar Factory - Ahmed, Nahid S.; Hassan, Kamal S.; EIKhalifa, Elamin A. (Gezira Journal of Engineering and Applied Sciences, 2018)
This study aimed to investigate the influence of mechanical harvest on juice clarification in Elguneid sugar factory. Elguneid factory was designed to treat a hand cut cane more than a mechanical cut cane. So, the clarification system was tuned to meet this purpose. Color, turbidity, reducing sugar, sugar content, purity, pH, brix, temperature and phosphate content were determined. The results showed: the color has increased from 3910 to 13921 ICUMSA, turbidity from 3242 to 8496 and reducing sugar increased to 0.928%. Sucrose content decreased from 14.39 to 11.69% and purity from 88 to 83%. The results of Pol% and Purity% were taken at the beginning of crushing season, where the mechanical harvest was higher than hand cut. A comparative study between hand cut and mechanical harvest was made at the middle of the crushing season. The optimum brix in the clarifiers matched the turbidity decreased at brix 12%, 13% respectively. Also from the tests carried out it was shown that the flocculant and phosphoric acid, which were used by the factory personnel was lower than the standard values, phosphoric acid was 183ppm and the polymer was 1,6ppm. These low values affected the precipitation process. There is a relationship between the amount of mud and type of harvest. It was noticed that there is a relationship between sugar yield and type of harvest.